An economic consideration of the Irish judgment - acts - Vereker, John P. (Statistical and Social Inquiry Society of Ireland, 1849)
It has frequently been asked, Why have the landlords of Ireland so deeply encumbered their estates? and why do they not now, by a sale of a portion of their property, release the remainder from their creditors? The last question has already been partly answered by the able papers read before this society, by Professor Hancock and Dr. Longfield, upon "the legal difficulties that impede the transfer and sale of landed property" in this country; but as I feel it would be quite impossible for me, in the short time during which I intend to trespass upon your indulgence, to give anything even approaching to a satisfactory answer to the remainder of these questions, I propose to confine myself altogether, in this paper to the economic effects of the judgment acts as they exist in Ireland.
Read March 19th 1849
Keywords: Judgement acts; Land leasing; 314.15